Cryptogenic Multifocal Ulcerous Stenosing Enteritis: A Review of the Literature. (24th November 2013) - Kohoutová, Darina; Bártová, Jolana; Tachecí, Ilja; Rejchrt, Stanislav; Repák, Rudolf; Kopáčová, Marcela; Bureš, Jan
Abstract : Cryptogenic multifocal ulcerous stenosing enteritis (CMUSE) is an extremely rare illness characterised by chronic or relapsing subileus status resulting from multiple small intestinal fibrous strictures and multiple shallow ulcers of the small bowel. The etiology is unknown and pathogenesis is not fully understood. Therapy with systemic glucocorticosteroids is the treatment of choice. However, most patients develop corticosteroid dependence. Deep enteroscopy enables precise diagnostic work, possible endoscopic treatment of stenoses; may obviate the need for surgery and prevent excessive small bowel resections.